Ed Ricketts - Unknown:::Creator::::::::::::
Ed 'Doc' Ricketts sitting between Toni Jackson and Betty Farmer on a rail fence. Slightly out of focus. Inscription on back mentions 'Stone & hotel.' Jackson lived with Ed. Ricketts for seven years.